The Amount of Joint Property Distribution of Polygamous Marriage in the Supreme Court Decision Number 82 PK/AG/2019: An Analysis of the Legal Objectives of Gustav Radbruch - Moch. Rizki Fadlillah; Erfaniah Zuhriah; Ali Hamdan (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
Joint property is wealth obtained during the marriage and its arrangements are contained in the Marriage Law and the Compilation of Islamic Law. However, the division of joint property in polygamous marriages is still generally regulated without a strict proportional formula, thus creating a vacuum of norms and legal uncertainty. To overcome this condition, the Supreme Court provides guidelines through Book II of the Guidelines for the Implementation of Duties and Administration of Religious Courts which regulates proportional distribution. However, these guidelines are not always used as a basis for judges' considerations, as seen in the Supreme Court Decision Number 82 PK/Ag/2019. This study aims to analyze the method of judges' legal findings in the division of joint property in polygamous marriages and assess their suitability based on Gustav Radbruch's Theory of Legal Objectives. This research is a normative legal research with a case and conceptual approach. The data was analyzed through a study of the Supreme Court Decision Number 82 PK/Ag/2019 using the theory of legal discovery and the theory of legal purpose Gustav Radbruch as the framework of analysis. The results of the study show that the judge's consideration has not reflected the application of clear and consistent legal norms because it overrides Book II of the Guidelines for Religious Justice and prioritizes the grammatical interpretation of Article 96 paragraph (1) of the Compilation of Islamic Law which is general. Judging from the perspective of Gustav Radbruch, the decision has not fully fulfilled the aspects of justice, utility, and legal certainty. Therefore, it is necessary to strengthen the normative position of Book II of the Religious Court Guidelines, the revision of the Compilation of Islamic Law related to the division of common property in polygamy, and the consistency of judges in integrating legal objectives in each decision.